2012
DOI: 10.1002/j.1532-2149.2012.00244.x
|View full text |Cite
|
Sign up to set email alerts
|

Guided Internet‐delivered cognitive behavioural therapy for chronic pain patients who have residual symptoms after rehabilitation treatment: Randomized controlled trial

Abstract: We conclude that Internet-delivered treatment can be partly effective for persons with residual problems after completed pain rehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
77
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(82 citation statements)
references
References 52 publications
0
77
1
1
Order By: Relevance
“…Several of the studies reported significant improvement in functioning and pain-related disability 17,20,21,25,37,42,44,46,[51][52][53]55 ; however, 10 studies 23,[38][39][40][41]43,45,47,57,58 did not find statistically significant improvement in physical functioning or disability in their intervention sample. At the 11-month follow-up assessment, Kristjansdottir et al 48 found a significant effect for the intervention condition in terms of physical functioning (FIQ) compared with baseline assessment; this effect was not seen at posttreatment in this sample.…”
Section: How Has the Internet Been Used For Treatment Of Chronic Noncmentioning
confidence: 99%
“…Several of the studies reported significant improvement in functioning and pain-related disability 17,20,21,25,37,42,44,46,[51][52][53]55 ; however, 10 studies 23,[38][39][40][41]43,45,47,57,58 did not find statistically significant improvement in physical functioning or disability in their intervention sample. At the 11-month follow-up assessment, Kristjansdottir et al 48 found a significant effect for the intervention condition in terms of physical functioning (FIQ) compared with baseline assessment; this effect was not seen at posttreatment in this sample.…”
Section: How Has the Internet Been Used For Treatment Of Chronic Noncmentioning
confidence: 99%
“…A recent review indicates that the treatment effects of ICBT are similar to the effects obtained in traditional face-to-face CBT (Hedman, Ljo´ts-son, & Lindefors, 2012). Accordingly, studies evaluating ICBT for chronic pain, based on coping strategies, have demonstrated small to moderate effects (e.g., Buhrman et al, 2012). However, studies have demonstrated that an ICBT protocol based on exposure principles presented within an ACT framework results in large effects on symptoms and quality of life for patients with irritable bowel syndrome (IBS; Ljo´tsson et al, 2010;Ljó tsson, Hedman, et al, 2011).…”
Section: Internet-delivered Acceptance and Values-based Exposure Treamentioning
confidence: 99%
“…With regards to behavioral interventions which now largely are considered the treatment of choice for persistent insomnia [33], cognitive-behavioral therapy addressing both pain and sleep, has been found to be effective [32]. Future research should examine to what extent low threshold interventions addressing comorbid sleep and pain may be effective, as internet-based self-help treatments have shown promising results in treating both conditions individually [34][35][36]. Moreover, given the significant contribution of depressive symptoms in explaining the observed sleep-pain association, we also recommend screening for depression during and after pregnancy, in addition to adequately identifying, preventing and treating insomnia for this population.…”
Section: Discussionmentioning
confidence: 99%